Сomparative analysis of the change of oxygen nonstoichiometry and superstructural ordering of Fe/Mo cations in the strontium ferromolybdate - L. I. Hurski; N. A. Kalanda; М. V. Yarmolich; А. V. Petrov; D. A. Golosov; М. V. Kirosirova; О. V. Ignatenko; А. L. Zhaludkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Sr2FeMoO6–δ single-phase samples without Fe/Mo cations superstructural ordering (P) and with Curie temperature 407 K were obtained by the solid-phase technique. According to the XRD data, the growth dynamics of the parameter P is nonlinear. In this case, the process of reaching maximum values of P (Pmax) is long and its rate is several times lower than the change of the oxygen index 6–δ. It was found that with increasing temperature of isothermal annealing, P increases and reaches maximal values 88 % at T = 1320 K for 120 h, Pmax = 92 % at T = 1420 K for 100 h, while Pmax = 90 % at T = 1470 K for 45 h. One can assume that the lower values of Pmax at T = 1470 K than at T = 1420 K are due to the influence of thermal energy on the destruction of chain ordering of Fe and Mo cations placed in staggered order. Based on the analysis of P time dependences, two relaxation processes can be found and the dP/dt = ¦(t) can be divided into two regions – I and II. In the region I the relaxation time is shorter than that in the region II. The point is that the ordering of cations in the –O–Fe–O–Mo–O chains in the region I requires atomic displacements by approximately one interatomic distance, whereas in the region II cation displacements occur over long distances with the formation of long[1]chain long-range ordering.